RANCANG BANGUN MEDIA PEMBELAJARAN GAME EDUKASI BERBASIS ANDROID PADA MATERI BANGUN DATAR UNTUK SISWA KELAS V SD NEGERI JERUK 2 MIRI SRAGEN TAHUN AJARAN 2024/2025 - Nanda Istiqomah; Hera Heru Sri Suryanti; Yudhistiro Pandu Widhoyoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study employed a Research and Development (R&D) method with the ADDIE development model. Data collection involved interviews, questionnaires, and documentation. Testing of the Android-based educational game learning media was conducted using the Blackbox Testing method and expert validation, converted using a Likert Scale. The results showed that the Android-based educational game learning media met the criteria of being very feasible according to media experts with a feasibility level of 89.33%. The validation by material experts with a feasibility level of 90.6%, with the criteria of being very feasible. The assessment by educators resulted in a percentage of 92.44%, with the criteria of being very feasible. Therefore, the educational game learning media is suitable for use as an alternative learning medium and entertainment tool for independent learning anytime and anywhere.